Bismillah Khan Maestro from Benaras - Sinha,Juhi (New Delhi Niyogi, 2011)
Bismillah Khan: Maestro from Benaras is an insightful look into the home and heart, and at the musical journey of one of the greatest artists that India has produced. The book follows the music legend Bismillah Khan as he grows from child to man, from pupil to legend. The book also lovingly portrays the whims and foibles of Bismillah Khan giving readers a glimpse of the wit, humour and charisma behind the artist.
Keywords: Biography:Bharat Ratna Awardee-Bismillah Khan